O immersyjności escape roomów. Przykład pokoi Tick Tack w Gliwicach - Julke-Bogacka, Katarzyna (Replay. The Polish Journal of Game Studies, 2017)
Escape room (ER) is a live cooperative game in which players need to find a way out of a closed room, or to reach an additional goal by solving a series of riddles and puzzles, in a set amount of time. So far there have been few publications on ERs, particularly in Polish game studies. This paper is an attempt at filling this gap. The history of ERs is described briefly, and the claim is made that the reason for the success and popularity of selected ERs is their immersivity. The rooms of the company Tick Tack, which is located in Gliwice, are used as examples to discuss the topic of ER immersivity and the conditions that a room should meet to engage players fully. The analysis is based on relevant literature and on the author’s own experiences with ERs.